2019
DOI: 10.1108/sef-11-2017-0315
|View full text |Cite
|
Sign up to set email alerts
|

Stock market performance and cross-border mergers and acquisitions in South Africa

Abstract: Purpose Since the attainment of fully fledged democracy in 1994, South Africa witnessed a substantial increase in both the number and the value of completed mergers and acquisitions (M&As) targeting South African firms. In spite of this development, studies on foreign direct investment (FDI) on South Africa have not looked at determinants of entry-mode choice of FDI such as M&A. The purpose of this paper is to fill the gap in the literature by investigating locational factors that make South Africa an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…GDP, interest rate and the unemployment rate were included in the models to examine and measure the economic activity effect (macroeconomic variables) on banking M&A decisions. Previous studies (Melicher et al , 1983; Guerard, 1989; Mitchell and Mulherin, 1996; Gaughan, 2011; Choi and Jeon, 2011; Wilson, 2013) have reported that GDP, interest rates and unemployment rate are important factors in merger activity. They observe a positive correlation with mergers.…”
Section: Research Design and Empirical Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…GDP, interest rate and the unemployment rate were included in the models to examine and measure the economic activity effect (macroeconomic variables) on banking M&A decisions. Previous studies (Melicher et al , 1983; Guerard, 1989; Mitchell and Mulherin, 1996; Gaughan, 2011; Choi and Jeon, 2011; Wilson, 2013) have reported that GDP, interest rates and unemployment rate are important factors in merger activity. They observe a positive correlation with mergers.…”
Section: Research Design and Empirical Resultsmentioning
confidence: 98%
“…Previous studies (Melicher et al, 1983;Guerard, 1989;Mitchell and Mulherin, 1996;Gaughan, 2011;Choi and Jeon, 2011;Wilson, 2013) have reported that GDP, interest rates and unemployment rate are important factors in merger activity. They observe a positive correlation with mergers.…”
Section: Regression Analysis (Testing H3)mentioning
confidence: 99%
“…Jongwanich et al (2013) examines the relationship between cross border M&A and financial development in emerging Asian countries from 2000 to 2009. It shows a positive correlation between cross border M&A inflow and exchange rate because if currency depreciation is more likely to be a destination for investment.Similarly,Wilson and Vencatachellum (2016) studied the determinant of cross border M&A in targeting Africa from 1990-2011. The result of the positive sign of exchange rate determinant means that domestic assets relatively low cost and then it boosts cross-border M&A inside the host country.…”
mentioning
confidence: 99%